Scolex morphology of the cestode Silurotaenia siluri (Batsch, 1786) (Proteocephalidae: Gangesiinae), a parasite of European wels (Silurus glanis) - Scholz, T; Zd'árská, Z; de Chambrier, A; Drábek, R (Parasitology research, 1999)
The morphology of the scolex of the tapeworm Silurotaenica siluri (Batsch, 1786) (Proteocephalidae: Gangesiinae), a specific parasite of European wels (Silurus glanis L.), was studied using light, scanning (SEM), and transmission electron (TEM) microscopy. The scolex of S. siluri is rather uniform in shape and size; it is globular, and has four prominent, anteriorly directed suckers and a spherical, muscular apical organ corresponding to the rostellum of cyclophyllidean cestodes. The rostellum-like apical organ is armed with five to six irregular rows of small hooklets with a wide, oval basal plate and a short, posteriorly curved blade. The excretory system of the scolex is formed by sinuous secondary canals ending blindly beneath the distal layer of the tegument, not opening outside. The surface of the scolex is covered with filiform microtriches; giant spine-like and blade-like microtriches, incorrectly interpreted as spines or hooklets in previous descriptions of S. siluri, are present on the neck region and posterior margins and internal cavities of the suckers. It is assumed that tegumental spines reported in the scolices of other proteocephalideans (subfamilies Acanthotaeniinae and Gangesiinae, genera Spasskyellina and Nomimoscolex) could indeed be spiniform microtriches.
Keywords: Cestoda; elektronová mikroskopie; Catfishes; Animals; sumci; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; zvířata; Microscopy, Electron